(untitled) (Czech Journal of International Relations, 2002)
The objective of the article is twofold: to shed more light on the concept of polarity and its current position and to set out the path which should be followed by research in the field of polarity if we wish to maintain polarity as a theoretically relevant category. The article looks at the definition of polarity as such and the definitions of the terms connected with polarity (polarisation and concentration). The author analyses developments in the understanding of polarity, with special attention paid to Morgenthau’s and Kaplan’s approaches, in order subsequently to turn to the most important part of the polarity debate, i.e. the relationship between polarity and system stability. The debate has long split researchers between advocates of stable multipolarity (e.g. Deutsch & Singer) and stable bipolarity (e.g. Waltz). There have been three major reactions to the inconclusive polarity/stability debate: The first group of researchers tried to find a solution with the help of behaviouralist methodology; others aimed at further elaborating the concept and thus enhancing its analytical usefulness, and yet another stream rejected the category entirely, viewing it as a tool with no satisfactory applicability. This article also analyses the current state of the debate. Much effort is dedicated to identifying the concept’s most troublesome deficiencies and suggesting some proposals for their solution. The most important proposed shifts are the disaggregation of power polarity, which would allow more exact polarity-measuring, loosening the ties of polarity to neorealism, and turning to a more historical description of reality, focusing on non-state actors in addition to states, and, possibly, elaborating some implications following from the research of "non-material" capabilities and changes in their polarity.